Diagnostic and early prognostic value of serum CRP and LDH levels in patients with possible COVID-19 at the first admission - Dogan Akdogan; Mustafa Guzel; Dervis Tosun; Orhan Akpinar (Journal of Infection in Developing Countries)
Introduction: COVID-19 is the infection caused by the new coronavirus. Specific treatment for COVID-19 has not been established, yet. It is important to determine the disease severity of the patients at the first admission. Therefore, the exploration of biomarkers is deemed necessary. We aimed to assess the diagnostic and early prognostic value of CRP and LDH levels in possible COVID-19 patients presenting with a severe clinical picture.